User perception on environmental friendly practices among primary schoolchildren in Perak - Savita, K.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this era, mobile devices are very popular and highly used among children for education and entertainment purposes. Environmental studies among children are still limited, especially in context of Malaysia. The usage of mobile devices among the children are high, and the exposure to mobile phone occurs at young age with the parental guidance. The early exposure is due to parent acknowledgment on the important to expose them with new technologies and to have hands-on over the technology for educational purposes. The preliminary findings obtained from a pilot study of 52 school children from a school in Perak state, Malaysia as indicated that students show high interest in using mobile application for education purposes. Despite lacking in environmental awareness, the schoolchildren are willing to learn with the use of interactive and intelligent mobile application since the schoolchildren are given access the mobile phone during their leisure time at home. They opt for features that increase their involvement, learning experience and span of attention in using the application. The initial designs of the mobile application are presented in this paper in order to provide the brief preview before proceeding further with development of the full application. The mobile application is known as 'Green UP Manager', act as an awareness platform to promote the schoolchildren towards positive behavior in assisting the Nation towards greening and protecting the environment towards sustainable future. Â© 2016 IEEE.